Raccoon John Smith : frontier Kentucky's most famous preacher - Sparks, John, 1961- (University Press of Kentucky, 2005)
Lexington, Kentucky, has the honor of being the birthplace of one of the first genuinely homegrown American Christian faiths: the Disciples of Christ. Established in 1832 by the union of two Christian groups led by Alexander Campbell and Barton W. Stone, their descendent churches are now referred to by religious scholars as the Stone-Campbell movement. In the state's best tradition, this historic movement soon acquired its own larger-than-life legend: Raccoon John Smith, the flamboyant frontier preacher of the southern Kentucky mountains. Smith moved to the lowland Bluegrass and braved conside.
Keywords: Smith, John, -- 1784-1868.; Disciples of Christ -- Clergy -- Biography.; Smith, John, -- 1784-1868; Disciples of Christ; RELIGION -- Christianity -- Baptist.; BIOGRAPHY & AUTOBIOGRAPHY -- Religious.; Clergy; Biographies; Biographies.